Enhancing cognitive function in older adults: dietary approaches and implications - Polis, Baruh; Samson, Abraham O. (Frontiers in Nutrition, 2024)
Natural aging encompasses physiological and psychological changes that impact overall health and quality of life. Mitigating these effects requires physical and mental exercise, coupled with proper nutrition. Notably, protein malnutrition emerges as a potential risk factor for senile dementia, with insufficient intake correlating with premature cognitive decline. Adequate protein intake in the elderly positively associates with memory function and lowers cognitive impairment risk. Considering diet as a modifiable risk factor for cognitive decline, extensive research has explored diverse dietary strategies to prevent dementia onset in older adults. However, conclusive results remain limited. This review aims to synthesize recent evidence on effective dietary approaches to enhance cognitive function and prognosis in older individuals. Specifically, the study evaluates complex multicomponent programs, protein-rich diets, and branched-chain amino acid supplementation. By addressing the nexus of nutrition and cognitive health, this review contributes to understanding viable interventions for promoting cognitive well-being in aging populations.